2016
DOI: 10.1108/ijcst-12-2014-0141
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the appearance of jackets with adhesive interlinings

Abstract: Purpose: This study quantitatively evaluates the effect of adhesive interlining on the appearance of tailored jackets with different rigidity.Design/methodology/approach: Four tailored jackets having the same pattern and fabric and three different adhesive interlinings or no adhesive interlining were prepared as experimental samples. Criteria and characteristics for assessing jacket appearance were investigated in sensory tests. A paired comparison of the jacket appearance was conducted using a ranking method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Therefore, when considering the appearance of a lady’s tailored jacket, wrinkling on the bust and sleeve and the silhouette fitting the body line are indices of fit evaluation. Kim et al (2015, 2016) found that waist constriction and wrinkles were criteria for the evaluation of a jacket’s appearance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, when considering the appearance of a lady’s tailored jacket, wrinkling on the bust and sleeve and the silhouette fitting the body line are indices of fit evaluation. Kim et al (2015, 2016) found that waist constriction and wrinkles were criteria for the evaluation of a jacket’s appearance.…”
Section: Resultsmentioning
confidence: 99%
“…Participants also explained their evaluation and stated the parts of the jacket that determined their evaluation. The jacket was divided into 31 parts as shown in Figure 4 to allow the participants to identify parts of the jacket (Kim et al , 2013, 2016). We selected images of even sizes from the pictures of jacket appearance observation to reduce the load for the evaluator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of sensory descriptors is crucial for characterizing products (Kim et al , 2016). A procedure is proposed as follows (Xue et al , 2014): The exhaustive expressions of all the trainees are collected without considering whether they make sense or not.…”
Section: Sensory Evaluation Methodsmentioning
confidence: 99%
“…Depending on allowance for ease, people’s judgments of the appearance of garments were found to vary in clothing selection (Ashdown and Delong, 1995; Monobe et al , 2017). For evaluation of fit in appearance, wrinkle and waist constrictions are considered important criteria (Kim et al , 2013, 2016).…”
Section: Introductionmentioning
confidence: 99%